A Perspective of ECE Teachers in Introducing Maritime Cultural Literacy for Early Childhood - Fahmy Ulfah Mawaddah; Hapidin; Rien Safrina (Universitas Panca Sakti Bekasi, 2023)
Indonesia is a maritime culture country but its population is more dominated by the land sector, if it continues to be allowed Indonesia will leave its culture which is a maritime culture. This study aims to describe the perspective of early childhood education teachers in introducing maritime cultural literacy in early childhood. The type of research used is descriptive qualitative. The method used is a case study. The research location was at Al-Hikmah Kindergarten, Kalaotoa Island. The research was conducted in April-June 2021. Data collection using interviews, observation and documentation. Interviews were conducted in depth with six early childhood education teachers who are native to the islands. The results showed that early childhood education teachers on the islands had a lack of access to maritime cultural literacy media for early childhood, therefore it was concluded that to improve maritime cultural literacy it was necessary to develop learning media that was appropriate and easily accessible to teachers. Learning media to facilitate early childhood education teachers can be done, among others, 1) a special website for early childhood maritime cultural literacy, 2) digital picture story media, or 3) visits to education units in the islands to introduce learning methods to improve maritime cultural literacy.